COMMUNITY EMPOWERMENT THROUGH EMBROIDERY TRAINING FOR WOMEN IN KUDAP VILLAGE, TASIK PUTRI PUYU DISTRICT, MERANTI ISLANDS REGENCY, RIAU PROVINCE - Zulfikar Hasan (Eastasouth Journal of Impactive Community Services, 2022)
The Kudap Village located in the Tasik Putri Puyu Sub-district,Meranti Islands Regency is One Of The Villages where the community is still in a developing condition. One of the ways to overcome these community problems is through community empowerment activities carried out, namely through embroidery training according to the needs of the community. The learning approach used in this training is an andragogy approach with discussion and practice methods the implementation of embroidery training activities at the home of one of the people of kudap village,tasik putri puyu district,meranti islands regency, which is carried out on august 20,2022. Mothers in the village of kudap in making embroidery thet can be used as a livelihood for the community.